Differential Programming of B Cells in AID Deficient Mice - Hogenbirk, Marc A.; Heideman, Marinus R.; Velds, Arno; van den Berk, Paul CM; Kerkhoven, Ron M.; van Steensel, Bas; Jacobs, Heinz (PloS one, 2013)
The Aicda locus encodes the activation induced cytidine deaminase (AID) and is highly expressed in germinal center (GC) B cells to initiate somatic hypermutation (SHM) and class switch recombination (CSR) of immunoglobulin (Ig) genes. Besides these Ig specific activities in B cells, AID has been implicated in active DNA demethylation in non-B cell systems. We here determined a potential role of AID as an epigenetic eraser and transcriptional regulator in B cells. RNA-Seq on different B cell subsets revealed that Aicda(-/-) B cells are developmentally affected. However as shown by RNA-Seq, MethylCap-Seq, and SNP analysis these transcriptome alterations may not relate to AID, but alternatively to a CBA mouse strain derived region around the targeted Aicda locus. These unexpected confounding parameters provide alternative, AID-independent interpretations on genotype-phenotype correlations previously reported in numerous studies on AID using the Aicda(-/-) mouse strain.